Fluorescence can be used to trace the fate of exogenous micro-organisms inside the alimentary tract of mosquitoes - Satho, Tomomitsu; Dieng, Hamady; Mizutani, Tetsuya; Eshita, Yuki; Miyata, Takeshi; Talukder, Parimal; Kashige, Nobuhiro; Abu Hassan, Ahmad; Miake, Fumio (Academic Journals, 2009)
There is a great deal of current research interest in utilising bacteria for the control of intractable arthropod-borne diseases such as dengue. Although there is accumulating evidence that bacterial infection is a promising control strategy, most studies on bacteria-insect interactions lacked useful markers for detecting pathogenesis. This provided the impetus to investigate bacterial infection in the dengue vector Aedes albopictus. The infection persistence patterns in key organs of the alimentary canal of females were examined using a GFP-expressing strain of Escherichia coli (Migula). Just after feeding with sugar meal containing the bacteria, the crop and midgut as well as parts of the Malpighian tubules showed fluorescence. From 1 h onwards, bacterial populations declined sharply in both the midgut and crop, with complete elimination in the former but persistence of bacteria at 7 h post-feeding in the latter. After 24 h, neither organ retained the fluorescent marker. However, culture of homogenates of these organs in Luria-Bertani medium revealed the presence of a bacterial population in the crop, but not in the midgut. These observations suggest a difference in the potential hysiological actions expressible by the two organs. In fact, both are storage sites for ingested fluids, but the midgut has greater physiological activity. Presumably, one of these activities contributed to eliminating GFPexpressing E. coli from the A. albopictus midgut after 24 h. The results of the present study using a fluorescent marker to detect infection may be useful for developing strategies to fully characterise the main steps involved in the bacterial infection process in insects.